Maternal colonization with group B Streptococcus and antibiotic resistance in China: systematic review and meta-analyses - Jing Wang; Yan Zhang; Miao Lin; Junfeng Bao; Gaoying Wang; Ruirui Dong; Ping Zou; Yuejuan Chen; Na Li; Ting Zhang; Zhaoliang Su; Xiuzhen Pan (BMC, 2023)
Abstract Background Maternal rectovaginal colonization with group B Streptococcus (GBS) or Streptococcus agalactiae is the most common pathway for this disease during the perinatal period. This meta-analysis aimed to summarize existing data regarding maternal colonization, serotype profiles, and antibiotic resistance in China. Methods Systematic literature reviews were conducted after searching 6 databases. Meta-analysis was applied to analyze colonization rate, serotype, and antimicrobial susceptibility of GBS clinical isolates in different regions of China. Summary estimates are presented using tables, funnel plots, forest plots, histograms, violin plots, and line plots. Results The dataset regarding colonization included 52 articles and 195 303 pregnant women. Our estimate for maternal GBS colonization in China was 8.1% (95% confidence interval [CI] 7.2%-8.9%). Serotypes Ia, Ib, III, and V account for 95.9% of identified isolates. Serotype III, which is frequently associated with the hypervirulent clonal complex, accounts for 46.4%. Among the maternal GBS isolates using multilocus sequence typing (MLST), ST19 (25.7%, 289/1126) and ST10 (25.1%, 283/1126) were most common, followed by ST12 (12.4%, 140/1126), ST17 (4.8%, 54/1126), and ST651 (3.7%, 42/1126). GBS was highly resistant to tetracycline (75.1% [95% CI 74.0-76.3%]) and erythromycin (65.4% [95% CI 64.5-66.3%]) and generally susceptible to penicillin, ampicillin, vancomycin, ceftriaxone, and linezolid. Resistance rates of GBS to clindamycin and levofloxacin varied greatly (1.0-99.2% and 10.3-72.9%, respectively). A summary analysis of the bacterial drug resistance reports released by the China Antimicrobial Resistance Surveillance System (CARSS) in the past 5 years showed that the drug resistance rate of GBS to erythromycin, clindamycin, and levofloxacin decreased slowly from 2018 to 2020. However, the resistance rates of GBS to all 3 antibiotics increased slightly in 2021. Conclusions The overall colonization rate in China was much lower than the global colonization rate (17.4%). Consistent with many original and review reports in other parts of the world, GBS was highly resistant to tetracycline. However, the resistance of GBS isolates in China to erythromycin and clindamycin was greater than in other countries. This paper provides important epidemiological information, to assist with prevention and treatment of GBS colonization in these women.